Bibliometric analysis of access journals open of Central America, the Caribbean and Mexico based in DOAJ and indexers Latin Americans - Fernández Eysseric, Madelaine Marie; Murillo González, Danny (Ingeniería Solidaria, 2019)
Introduction: This article is a product of the research on “The bibliometric analysis of Central America and Caribbean journals” that takes place at the Technological University of Panama in 2018.Objective: to measure the impact of open access journals and compare the countries of the study region. Also study the position of the magazines in Panama with respect to the other countries of the region.Methodology: We used the data from the indexed journals in DOAJ extracted in CSV format that were filtered by countries in a total of 211 journals and compared with indexers Latindex, Redalyc, Scielo and Redib in a total of 42 journals which were analyzed bibliometrically a Through the publish or perish software.Results: Most of the journals of the study region that belong to DOAJ comply with the necessary guidelines to index in the regional directories, however, of the 211 journals analyzed, only 42 have been integrated to the 4 indexers.Conclusions: The visibility of journals in the study region has improved the visibility of their publications, however, compared to countries such as Brazil, Indonesia and the United Kingdom, it is lower in impact numbers.Originality: In Panama there are no studies to measure scientific production or the impact of journals.Limitations: No data on this topic has been found in engineering publications.